FROM “SUFI ORDER RITUAL” TO INDONESIAN ISLAM (State Islamic University (UIN) of Sunan Ampel Surabaya, 2013)
BOOK REVIEWBook Title:Nur Syam, Tarekat Petani: Fenomena Tarekat Syattariyah Lokal (Yogyakarta: LKiS, 2013), xvi + 236;Achmad Chodjim, Sunan Kalijaga, New Edition (Jakarta: Serambi Ilmu Semesta, 2013), 371;Muzamil Qomar, Fajar Baru Islam Indonesia? (Bandung: Mizan 2012), xiii + 286